2019
DOI: 10.21608/zvjz.2019.14077.1052
|View full text |Cite
|
Sign up to set email alerts
|

Avipoxvirus in Egypt and African continent: A review

Abstract: Fowl pox disease is a slow-spreading viral infection of wild and domesticated birds of both genders, all ages and breeds. The disease occurs in two distinct forms; the more common cutaneous or dry form and the less common diphtheritic form. Fowl poxvirus (FWPV) is a member of the Avipoxvirus (APV) and it is one of the greatest challenges facing the poultry industry, its incidence is higher in tropical and subtropical countries. It causes a significant level of morbidity and increased mortality, especially in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…The molecular detection using PCR is widely accepted as a sensitive, specific, and rapid molecular tool for the detection of APV genomes [46,59]. In this regard, several studies have documented the isolation of APVs from poultry in Egypt [44,48,49]. Our present molecular findings revealed that the APV P4b gene was successfully amplified from all 40 tested isolates, which is in agreement with that obtained in previous studies [21,22].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The molecular detection using PCR is widely accepted as a sensitive, specific, and rapid molecular tool for the detection of APV genomes [46,59]. In this regard, several studies have documented the isolation of APVs from poultry in Egypt [44,48,49]. Our present molecular findings revealed that the APV P4b gene was successfully amplified from all 40 tested isolates, which is in agreement with that obtained in previous studies [21,22].…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with PGPV, it was considered to be different from FWPV, as they showed host specificity and different profiles with the nucleotide sequence analysis of the P4b gene [24,25,66]. Interestingly, the mans17P isolate identified in the present study showed 100% identity to other PGPVs obtained from GenBank, while the PGPV identified in this study was different from FWPV (mans17F), TKPV (mans17T), and CNPV (mans17C), with 91.7% identity and 44 nucleotide substitutions [4,22,44].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Avian pox is an important viral disease with a high incidence in tropical and subtropical countries 1 . Caused by a double-stranded DNA virus of the genera Avipoxvirus from the Poxviridae family, which infects and produces clinical signs in numerous domestic and wild birds 2 , 3 .…”
Section: Introductionmentioning
confidence: 99%